Propuesta de procesos para envasado y almacenamiento en la vida útil de tres bebidas ancestrales con preparados enzimáticos. - Tasiguano Cantuña, Heidy Karina (2020)
Theproposedinvestigationofprocessesforthepackaging and storage in theshelflifeofthree ancestral beverageswithenzymepreparationsaimedtoraiseinformationontheelaboration, heattreatments, typesofcontainers, packaging, storagetemperatures, and thedifferenttypesofphysicalanalysischemical, microbiological, bromatological and sensory, whichwould serve forfutureresearch and thusstartthe experimental research, executingalltheelaborationprocesses and cooking time of ancestral drinkswithintheinvestigationsthatwereinvestigated, ancestral drinksshould lead toaninactivation and / orpasteurization (sloworfast) ofthefermentingenzymespresent in thedrink at a temperaturegreaterthan 95 °C for 5 minutes (fast) or 65 ° C for 15 minutes (slow), then a rapidcoolingto a temperatureof4 ° C. Themostusedcontainers in thebeverageindustry are: glass and PET plastic, as they are resistanttocontrolledtemperaturechanges and are packagedbothartisanal and industrially in presentationsof 200ml, ° C, storageisanimportantprocessforthedeterminationoftheshelflife in beverages, therefore, anambienttemperatureof 20 ° C wasproposed and in refrigeration at 4 ° C where a correctrecordoftemperature control should be kept, withinthestorage time of ancestral beverages, itwasproposedperformphysical-chemicalanalysissuchas:pH, ºBrix , degreesof alcohol and microbiologicalsuch as: molds and yeastseverythreedaystoalltreatments, discardingtreatmentsthat do notcomplywiththeNTE standard INEN 2262. Forthetreatmentsthatcomplywithinanestimated time withthe standard, thephysical-chemicalanalysisiscarriedoutsuch as: pH, brix, and degreesof alcohol, microbiologicalsuch as: total coliforms, Escherichiacoli, mesophilicaerobes, molds and yeasts, Bromatologicalssuch as: protein, fat, fiber, ash and a sensoryevaluationsuch as colour, odor, taste and acceptability, throughtheseevaluationssomeoftheproducts can be acceptedorrejected.